High-Temperature Optical Fiber Sensor Fabricated by Water-Assisted Femtosecond Laser. Issue 208 (12th June 2020) - Ren, Yanqin; Liu, Lili; Wang, Min; Zou, Meng
Abstract: A miniaturized inline Fabry-Perot interferometer fabricated by fs laser direct writing in the water has been proposed. The performances of the Fabry-Perot interferometers fabricated in the deionized water and air have been investigated and the experimental results demonstrate that the sensor made in the water has better performance. The influence of the cavity length on the sensitivity is discussed as the temperature increases from 50 °C to 500 °C. The sensor fabricated in the water can be used as a high-temperature sensor in harsh environments due to its miniaturized size, high linearity, good repeatability and perfect mechanical property.